1991
DOI: 10.1128/mr.55.1.80-122.1991
|View full text |Cite
|
Sign up to set email alerts
|

Poxvirus pathogenesis

Abstract: Poxviruses are a highly successful family of pathogens, with variola virus, the causative agent of smallpox, being the most notable member. Poxviruses are unique among animal viruses in several respects. First, owing to the cytoplasmic site of virus replication, the virus encodes many enzymes required either for macromolecular precursor pool regulation or for biosynthetic processes. Second, these viruses have a very complex morphogenesis, which involves the de novo synthesis of virus-specific membranes and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
3

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(48 citation statements)
references
References 382 publications
0
45
0
3
Order By: Relevance
“…Variola and vaccinia are closely related members of Orthopoxvirus, a genus of viruses within the family Poxviridae. 8 Poxviruses are large and complex brickshaped viruses consisting of a core of viral DNA, lateral bodies, an outer membrane containing tubular-shaped lipoprotein subunits, and an envelope. 9 Poxviruses use…”
Section: Virologymentioning
confidence: 99%
“…Variola and vaccinia are closely related members of Orthopoxvirus, a genus of viruses within the family Poxviridae. 8 Poxviruses are large and complex brickshaped viruses consisting of a core of viral DNA, lateral bodies, an outer membrane containing tubular-shaped lipoprotein subunits, and an envelope. 9 Poxviruses use…”
Section: Virologymentioning
confidence: 99%
“…The role that ATI bodies play in the life cycle of many poxviruses is unclear [28,72,73], but it has been suggested that they might be involved in viral transmission or dissemination processes [74][75][76][77][78][79]. The predicted functional differences in ECTV-H as compared to ECTV-M are restricted to two conservative amino acid changes, an insertion of a repeated amino acid motif in EVM025 and the expression of a full-length p4b protein (Table 5, Table S3).…”
Section: In Vivo Dissemination and Transmission Of Ectv-m Is More Efficient Than Ectv-hmentioning
confidence: 99%
“…Studies have found that knocking out the BBK gene in VACV leads to a decrease in the number of mature progeny viruses ( 36 ). VACV bearing a BBK gene knockout mutation showed reduced toxicity in the nasal cavities of infected mice.…”
Section: Poxvirus-encoded E3 Ubiquitin Ligases and Adaptor Proteinsmentioning
confidence: 99%